Analisis Faktor-Faktor Yang Mempengaruhi Impor Beras Di Indonesia - Ratna Elsa Purwandari; Bagus Adhitya; Anisa Fatmawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Indonesia is one of the thrid largest rice producers after India and China, but Indonesia still imports to other countries because Indonesia's population countinues to increase. This study aims to determine the influience of harvested land area, pupulation, rice production, rice consumption, local rice prices, national rice reserves and cassava prices on rice imports in Indonesia. Hypotesis testing with multiple linear regression with help of eviews 12. The data used is a time series between 1980-2022 for 43 years. Research data is sourced from the Food Agriculture Organization (FAO), the Ministry of Trade, BPS, scientific journals and various other websites. The results showed that the area of harvested land, population, rice production, rice comsumtion, local rice prices, national rice reserves and cassava prices simultaneously have a significant influence on rice imports. Partially, the varibeles of harvested land area, national rice reserves, population, local rice prices, and cassava prices have a significant effect on rice imports in Indonesia. Variable rice production and comsumtion have an insignificant influence on rice imports in Indonesia. The implication of this study is that with the renewal of years and variables of rice subtitution goods, it is hoped that the goverment can apply effectively and effeciently, this is because it will have an impact on reducing imports, so that Indonesia does not continue to depend on other countries